2012
DOI: 10.1002/ijc.27973
|View full text |Cite
|
Sign up to set email alerts
|

miQ—A novel microRNA based diagnostic and prognostic tool for prostate cancer

Abstract: Today, the majority of prostate tumors are detected at early stages with uncertain prognosis. Therefore, we set out to identify early predictive markers of prostate cancer with aggressive progression characteristics. We measured the expression of microRNAs (miRNA) using qRT-PCR in formalin fixed and paraffin embedded prostatic tissue samples from a Swedish cohort of 49 patients with prostate cancer and 25 without cancer and found seven of 13 preselected miRNAs to discriminate between the two groups. Subsequent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
91
1
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 83 publications
(98 citation statements)
references
References 37 publications
4
91
1
2
Order By: Relevance
“…It is fundamental to increase the knowledge of how CRPC tumours progress so that patient morbidity can be reduced by newly developed therapies. In previous studies, we and others have observed downregulation of miR-145 in prostate cancer (9)(10)(11). Studying the correlation to clinical parameters in depth, we noted that miR-145 is associated with failure of androgen deprivation treatment, i.e.…”
Section: Introductionmentioning
confidence: 55%
See 1 more Smart Citation
“…It is fundamental to increase the knowledge of how CRPC tumours progress so that patient morbidity can be reduced by newly developed therapies. In previous studies, we and others have observed downregulation of miR-145 in prostate cancer (9)(10)(11). Studying the correlation to clinical parameters in depth, we noted that miR-145 is associated with failure of androgen deprivation treatment, i.e.…”
Section: Introductionmentioning
confidence: 55%
“…The level of miR-145 have previously been found to be significantly decreased in prostate cancer specimens in our Swedish cohort (9). Here, the prognostic value of miR-145 expression levels, as measured by qRT-PCR, was investigated in the same cohort.…”
Section: Expression Of Mir-145 Correlates To Prostate Cancer Prognosismentioning
confidence: 92%
“…miR-183 increases microRNA and protein levels of prostate-specific antigen Three miRNAs increasing PSA levels and predicted to target KLK3, miR-183 predicted to target the 3 0 UTR and upregulated in PCa patients [18], miR-650 predicted to target the CDS and promote tumourigenicity in gastric cancer [22], and miR-423 predicted to target the promoter and increase in metastatic breast cancer patients [23], were selected for further validation. Both secreted and intracellular levels of tPSA and fPSA were increased in PCa cells on transfection with mimic-miR-183, mimic-miR-423, and mimic-miR-650 compared with the scramble control ( Fig.…”
Section: Systematic Analyses Of Micrornas Regulating Prostatespecificmentioning
confidence: 99%
“…For example, the downregulation of miR-205 is useful in distinguished melanoma from nevus (Kozubek et al, 2013). Moreover, the relative expression of miR-205-5p in any Gleason pattern was decreased significantly compared with normal tissues (Tsuchiyama et al, 2013), to include prostate cancer samples compared with non-prostate cancer samples (Larne et al, 2013). These results could be explained by a previous report that miRNA expression profiles are tissue-specific (Lu et al, 2005).…”
Section: Discussionmentioning
confidence: 81%
“…While NPC miRNA expression studies have highlighted the importance and potential roles of miRNAs in disease, a deeper understanding is needed (Liu et al, 2013b). miR-183-5p was reported to be an early predictive biomarker for prostate cancer with aggressive progression characteristics (Larne et al, 2013), while conversely in lung cancer its expression was decreased . The tumor suppressor PTEN (phosphatase and tensin homolog deleted on chromosome ten) is known to be regulated by miR-183-5p (Sarver et al, 2010).…”
Section: Discussionmentioning
confidence: 99%